1993
DOI: 10.1002/dvg.1020140105
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two Maize HSP90 heat shock protein genes: Expression during heat shock, embryogenesis, and pollen development

Abstract: We have isolated two genes from Zea mays encoding proteins of 82 and 81 kD that are highly homologous to the Drosophila 83-kD heat shock protein gene and have analyzed the structure and pattern of expression of these two genes during heat shock and development. Southern blot analysis and hybrid select translations indicate that the highly homologous hsp82 and hsp81 genes are members of a small multigene family composed of at least two and perhaps three or more gene family members. The deduced amino acid sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 52 publications
6
42
0
3
Order By: Relevance
“…Recently, Queitsch et al (2002) showed that HSP90 may act as a capacitor, as had been proposed previously in Drosophila (Rutherfort and Lindquist, 1998). Genes encoding HSP90, along with their pattern of expression at the mRNA level, have been reported in maize (Marrs et al, 1993), barley (Walther-Larsen et al, 1993), tomato (Koning et al, 1992), periwinkle (Schroder et al, 1993), Brassica (Krishna et al, 1995;Neumann et al, 1993;Reddy et al, 1998), Arabidopsis (Conner et al, 1990;Takahashi et al, 1992), Pharbitis (Felsheim and Das, 1992), and rye (Schmitz et al, 1996), but the functional signi®cance of their expression patterns is not clear. In Arabidopsis, there are at least six HSP90 genes in addition to CR88.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, Queitsch et al (2002) showed that HSP90 may act as a capacitor, as had been proposed previously in Drosophila (Rutherfort and Lindquist, 1998). Genes encoding HSP90, along with their pattern of expression at the mRNA level, have been reported in maize (Marrs et al, 1993), barley (Walther-Larsen et al, 1993), tomato (Koning et al, 1992), periwinkle (Schroder et al, 1993), Brassica (Krishna et al, 1995;Neumann et al, 1993;Reddy et al, 1998), Arabidopsis (Conner et al, 1990;Takahashi et al, 1992), Pharbitis (Felsheim and Das, 1992), and rye (Schmitz et al, 1996), but the functional signi®cance of their expression patterns is not clear. In Arabidopsis, there are at least six HSP90 genes in addition to CR88.…”
Section: Discussionmentioning
confidence: 84%
“…Ia), a gene-specific oligonucleotide probe for the small heat-shock protein hsp17.9 (Marrs et al, 1993), the PCRderived fragment within the first exon of the maize GST I11 gene (GST) prepared for this study using the sequence reported by Moore et al (1986), and the cDNA plasmids for the maize C2 gene pC2-c46 (Wienand et al, 1986), the Adhl gene pB428 (Bennetzen et al, 1984), the B z l gene pMBzRl (Klein et al, 1989), and the vbcS gene pTN20 (a gift from Tim Nelson, Yale University, New Haven, CT). Probes were 32P-labeled using the oligolabeling kit supplied by Pharmacia.…”
Section: Rna Lsolation and Northern Blot Analysismentioning
confidence: 99%
“…As a control, RT-PCR was also performed using primers spanning the intron of the maize hsp82 gene to test the expression of an endogenous cadmium-inducible gene. Primers hsp82f and hsp82r span the single 140-bp intron of maize hsp82 (Marrs et al, 1993) and amplify a 380-bp fragment from the spliced transcript and a 520-bp fragment from the unspliced transcript. The sequences of these primers are: hsp82f (forward primer), S'-GTGCACATGGCTGGCGGTGC, and hsp82r (reverse primer), 5'-GGACTTGGTCATGCCCACGCC.…”
Section: Construction Of the Bz2:actin Fusion Construct And Expressiomentioning
confidence: 99%
See 1 more Smart Citation
“…The proteins are localized in different cell compartments, including the cytoplasm, the endoplasmic reticulum, and chloroplasts (Koning et al, 1992;Takahashi et al, 1992;Marrs et al, 1993;Schrö der et al, 1993;Krishna et al, 1995;Schmitz et al, 1996;Milioni and Hatzopoulos, 1997). The corresponding genes were shown to be specifically expressed during embryogenesis, pollen development (Marrs et al, 1993), and seed germination (Reddy et al, 1998) in young and rapidly divid-ing tissues such as shoot and root apices (Koning et al, 1992) and in flowers (Takahashi et al, 1992;Krishna et al, 1995). In oilseed rape (Brassica napus) and tomato (Lycopersicon esculentum) seedlings, HSP90 protein levels were found to increase by exogenous 24-epibrassinolide application (Dhaubhadel et al, 1999), whereas a glucosinolate-deficient Arabidopsis mutant was shown to be thermosensitive and defective in the cytosolic HSP90 expression after heat stress (Ludwig-Muller et al, 2000).…”
mentioning
confidence: 99%